Application of naskashima's 2 stages 4thorder pseudo-runge-kutta nethomethod and naksahima's 3 stages 5th" pseudo-runge-kutta method incorporate with hermite interpolation to delay problems - 280873 Nazeeruddin Yaacob; Universiti Teknologi Malaysia. Fakulti Sains. Jabatan Matematik (2011)
PSZJBL